Science, technology and magic in The witcher: a medievalist spin on modern monsters - Larsen, Kristine (Critical explorations in science fiction and fantasy, 2023)
"As Andrzej Sapkowski was fleshing out his character Geralt of Rivia for a writing contest, he did not set out to write a science textbook--or even a work of science fiction. However, the world that Sapkowski created in his series The Witcher resulted in a valuable reflection of real-world developments in science and technology. As the Witcher books have been published across decades, the sorcery in the series acts as an extension of the modern science it grows alongside. This book explores the fascinating entanglement of science and magic that lies at the heart of Sapkowski's novel series and its widely popular video game and television adaptations. This is the first English-language book-length treatment of magic and science in the Witcher universe, examining it through the lenses of politics, religion, history and mythology. Sapkowski's richly detailed universe investigates the sociology of science and ponders some of the most pressing modern technological issues, such as genetic engineering, climate change, weapons of mass destruction, sexism, speciesism and environmentalism. Notably, chapters explore the unsettling realization that the greatest monsters are frequently human, and their heinous acts often involve the unwitting hand of science"--